Hybrid plasmonic CH3Nh3PbI3 perovskite solar cells - Khue Viet, Le Thanh (2015)
In this project, we investigated the exciton-plasmon couplings in hybrid plasmonic perovskite CH3NH3PbI3 solar cells. The large exciton binding energies in the perovskite material system makes it ideal to investigate these couplings. Presently, it is unclear if the presence of plasmonic entities will help enhance the device efficiencies to beyond 20%. To get a better understanding of plasmonic effect on perovskite solar cells, we performed optical spectroscopy – steady state and time resolved photoluminescence effect on these samples and elucidate the energetics and the coupling mechanisms of the system.